Hydrophilic platinum(II) complexes containing 5, 7-dimethyl-1, 2, 4-triazolo[1, 5-a]pyrimidine: Spectroscopic and in vitro cytotoxic characterization. (15th November 2022) - Łakomska, Iwona; Hoffmann, Kamil; Sitkowski, Jerzy
Graphical abstract: Four platinum(II) complexes containing 5, 7-methyl-1, 2, 4-triazolo[1, 5- a ]pyrimidine (dmtp) of the general formula cis- [Pt(X)2 (dmtp)2 ], where X – acetato (1), trichloroacetato (2), trifluoroacetato (3), nitrato (4) have been isolated and characterized by spectroscopical methods 1 H, 13 C, 15 N, 195 Pt NMR and IR). Hydrophilic platinum(II) complexes (1–4), revealed rather moderate in vitro cytotoxicity. Highlights: Role of platinum(II) complexes in creation of chemotherapeutic prodrugs. Influence of type of leaving ligand on lipophilicity, and in vitro cytotoxicity. Abstract: Mononuclear platinum(II) complexes with 5, 7-methyl-1, 2, 4-triazolo[1, 5- a ]pyrimidine (dmtp) of the general formula cis- [Pt(X)2 (dmtp)2 ], where X - acetate (1), trichloroacetate (2), trifluoroacetate (3), nitrate (4) have been synthesized and characterized by multinuclear magnetic resonance ( 1 H, 13 C, 15 N, 195 Pt) and infrared spectroscopy methods. Spectroscopic parameters indicated the presence of the PtO2 N2 chromophore system with two monodentate N(3)-bonded 5, 7-methyl-1, 2, 4-triazolo[1, 5- a ]pyrimidines, and two monodentate O-donor ligands (carboxylate or nitrate). A cytotoxicity assay of hydrophilic platinum(II) complexes (1–4) against three human tumour cell lines A549 (non-small cell lung carcinoma), T47D (breast cancer), HT-29 (colon adenocarcinoma), and normal murine embryonic fibroblast cells (BALB/3T3) was performed. Considering the cytotoxic parameters of the studied complexes, the best in vitro results against the human breast tumour cells (T47D) were found for cis- [Pt(OOCCCl3 )2 (dmtp)2 ] although all the tested complexes (except complex (4) ) exhibited moderate in vitro activity.